Prevalence and components of metabolic syndrome in HIV-infected patients at the Tiko Central Clinic and Cottage Hospital in Cameroon - Njongang, Vigny N.; Nguedia, Assob J. C.; Walter, Ojong E. (International Journal of Research in Medical Sciences, 2020)
Background: HAART and HIV related metabolic syndrome (MS) is associated with increased cardiovascular risk in aging HIV patients. This study was aimed at comparing the prevalence of MS between HIV-infected patients on HAART and apparently healthy HIV-uninfected individuals and identifying key MS components in these groups of subjects. Methods: This was a hospital-based case-control study. The cases were HIV sero-positive individuals on HAART for at least 6 months and controls were HIV sero-negative individuals. Results: 74/135 (54.8%) participants were females amongst which 53/75 (70.7%) and 21/60 (35%) were in the test and control groups respectively. The prevalence of MS was insignificantly higher in HIV-infected patients on HAART than in control subjects according to the IDF (22.7% versus 20%, p=0.834) and NCEP ATP III criteria (18.7% versus 18.3%, p=1.000) respectively. The most prevalent components of MS in HIV-infected patients on HAART were low HDL-c (100%), abdominal obesity (IDF: 68%, ATP III: 32%), and hypertension (28%). Multivariate analysis of MS components in HIV-infected patients on HAART revealed that hypertension (OR: 15.996, 95% CI: 3.385-75.585; p≤0.001) and high blood glucose (OR: 10.760, 95% CI: 1.642-70.505; p=0.013) were associated with MS. Significantly more HIV-infected females were seen with abdominal obesity than HIV-infected males (86.8% versus 4.5%, p≤0.001). Conclusions: Abdominal obesity is a driving component of MS in HIV-infected patients particularly among females and hypertension is a prevalent and predictor component of MS among HIV patients.